Assessment of a decontamination process for dioxins and dioxin‐like PCBs in fish oil by physical filtration with activated carbon. (31st July 2017) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hoogenboom, Laurentius (Ron); et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Contaminants in the Food Chain (CONTAM) provided a scientific opinion on the assessment of a decontamination process consisting in the adsorption with activated carbon and physical filtration of fish oil in order to reduce the amount of dioxins (polychlorinated dibenzo‐ p ‐dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs)) and dioxin‐like polychlorinated biphenyls (DL‐PCBs). All feed decontamination processes must comply with the acceptability criteria specified in the Commission Regulation (EU) 2015/786. The data provided by the feed business operator were assessed with respect to the efficacy of the process and on information demonstrating that the process does not adversely affect the characteristics and the nature of the product. As described in scientific literature, the process was effective in removing PCDD/Fs (84%) and DL‐PCBs (55%), and therefore, it is possible to meet the current EU requirements with respect to these contaminants, assuming that the level of contamination of untreated fish oil was within the range of the tested batches. The Panel considered that the reference to information available in published literature was a pragmatic approach to demonstrate that the use of activated carbon adsorption does not lead to any detrimental changes in the nature of the fish oil; however, it was noted that the process could deplete some beneficial constituents (e.g. vitamins). Information was provided to demonstrate the safe disposal of the waste material. The CONTAM Panel concluded that on the basis of the information submitted by the feed business operator the proposed decontamination process to remove dioxins (PCDD/Fs) and DL‐PCBs from the fish oil by means of physical filtration with activated carbon, was compliant with the acceptability criteria provided for in Commission Regulation (EU) 2015/786 of 19 May 2015.